Microstructural properties and grinding of γ-Al2O3 and coal for environmental applications. (18th August 2019) - Cheng, Cheng; Adegbite, Stephen; Oladejo, Jumoke
ABSTRACT: The amphoteric characteristics of some metal oxides complemented by their chemical microstructures form the basis for their use for environmental engineering applications, e.g., alumina as catalyst and abrasive agents. This paper describes the microstructural properties and grinding behavior of γ -Al2 O3 and coal particles in a batch impact mill. By grinding γ -Al2 O3 and Hunan coal separately in an impact mill, a grinding process model of two dimensionless groups ∏ 1 ∗ and ∏ 2 is developed using Buckingham Pi theorem to obtain the desired particle morphologies. The properties established in this grinding model as key determinants of the grinding behavior are particle hardness, particle density and milling speed. The milling results confirm that γ -Al2 O3 of the HBW 5/100 hardness 247 show higher resistance to grinding than coal of HBW hardness 28, because the final ground particle diameters d 0.9 after 30 min milling were 136.6 and 33.4 µm for γ -Al2 O3 and coal, respectively. This grinding model is pioneering as the particle hardness contained in the dimensionless group ∏ 1 ∗ embodies an intrinsic material property which controls grinding and is confirmed to be in agreement with the fragmentation pattern.